On the Moving of Neutral Point for Mn Subject to Submerged Arc Welding under Various Heat Inputs: Case Study into CaF2-SiO2-Na2O-MnO Agglomerated Fluxes - Zhang, Dan; Shao, Guoyou; Zhang, Jin; Liu, Zhongqiu (Processes, 2022)
Neutral Point indicates the flux formula where no transfer of alloying element between the flux and weld metal occurs. For the submerged arc welding process, Neutral Point is an essential definition for flux design and specification since it helps to identify the flux microalloying ability. The scientific hypothesis that the Neutral Point is only a function of the flux formula is considered as the basis of the Mitra kinetic model. Within this framework, by performing submerged arc welding with CaF2-SiO2-Na2O-MnO agglomerated fluxes under various heat inputs, the moving of Neutral Point has been captured, indicating the scientific hypothesis proposed in Mitra kinetic model may be revised under high heat input welding. Additionally, although some studies have incorporated the consideration of the gas-slag-metal equilibrium, only the effective equilibrium temperature of 2000 or 2100 °C is utilized, which may be insufficient to constrain Mn content in the weld metal. In this study, we have incorporated all possible effective equilibrium temperatures that may be attained in the submerged arc welding process to simulate the transfer behavior of Mn. Then, a novel thermodynamic approach is proposed to detect the moving direction of Neutral Point for Mn from both slag-metal and gas-slag-metal equilibrium considerations, which may pave a vital way for the flux design and the setting of welding parameters. The factors responsible for the deviation between real and predicted data are discussed. The mechanism responsible for the moving of Neutral Point regarding the Mn element is evaluated from the perspective of both slag-metal and gas-slag-metal equilibrium considerations.